Potential Modulatory Microbiome Therapies for Prevention or Treatment of Inflammatory Bowel Diseases - Daan V. Bunt; Adriaan J. Minnaard; Sahar El Aidy (MDPI AG, 2021)
A disturbed interaction between the gut microbiota and the mucosal immune system plays a pivotal role in the development of inflammatory bowel disease (IBD). Various compounds that are produced by the gut microbiota, from its metabolism of diverse dietary sources, have been found to possess anti-inflammatory and anti-oxidative properties in in vitro and in vivo models relevant to IBD. These gut microbiota-derived metabolites may have similar, or more potent gut homeostasis-promoting effects compared to the widely-studied short-chain fatty acids (SCFAs). Available data suggest that mainly members of the Firmicutes are responsible for producing metabolites with the aforementioned effects, a phylum that is generally underrepresented in the microbiota of IBD patients. Further efforts aiming at characterizing such metabolites and examining their properties may help to develop novel modulatory microbiome therapies to treat or prevent IBD.